Dragon of the red dawn - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2007)
When Merlin is weighed down by sorrows, Jack and Annie travel back to feudal Japan to learn one of the four secrets of happiness.
"A Merlin mission."
"A Stepping Stone book."
Keywords: Time travel; Magic; Happiness; Brothers and sisters; Time travel; Magic; Happiness; Brothers and sisters